Pancasila dan tantangan keadilan sosial di era digital - nadriyah, yusfi (Maliki Interdisciplinary Journal, 2026)
Pancasila as the state foundation of Indonesia holds an important role in creating social justice, especially amidst the rapid development in the digital era. In this regard, the fifth principle of Pancasila, "Social Justice for All Indonesian People," serves as a foundation to ensure everyone has equal access to resources and opportunities in the digital society. This article examines how Pancasila values can be applied to address the challenges of the digital divide, maintain ethics and morality in social interactions in the virtual world, and advance the transformation towards the digital revolution. By using technology wisely and fairly, and by prioritizing the principles of humanity and social justice, Indonesia can overcome global challenges while maintaining its national identity based on the noble values of Pancasila. This research aims to provide deeper insight into the importance of Pancasila in the contemporary context and its role in achieving social justice in the digital era.